U.S. Corporate Interests and the Political Economy of Trade Policy - Pugel, Thomas A.; Walter, Ingo (The Review of Economics and Statistics, 1985)
This paper examines the behavior of American corporations with respect to international trade policy initiatives during the 1970s using survey-generated data on revealed corporate trade policy interests and firmand industry-level data on company characteristics. Direct or proxy variables were developed and applied in linear regression equations using an ordered probit specification, and in an alternative approach using factor analysis to construct a composite dependent variable. Hypothesized relationships were verified between corporate positions on trade liberalization and the intensity of competition from imports, the benefits from improved access to foreign markets, and internal risk-pooling capabilities of firms. FIRMS exposed to the international competitive environment inevitably have a stake in national trade policy. This paper explores the revealed behavior of U.S. corporations on matters of trade policy in the 1970s. It develops a set of hypotheses linking corporate trade-policy positions to a series of company and industry attributes. These hypotheses are tested using survey-generated information regarding corporate behavior on trade policy matters beginning with the protectionist Burke-Hartke initiatives of the early 1970s through the post-Tokyo Round period at the end of the decade. Studies of the political economy of protection typically begin with the proposition that import barriers create rents that can be appropriated by the protected industry. The size of the rents to be obtained and their probable division among the various participants in the industry partly determine the intensity of protection-seeking behavior (lobbying) undertaken by participants in the industry (Brock and Magee, 1978). The intensity is also influenced by the degree of success expected in the political arena, and by imperfections in the lobbying process-for instance, the incentive to be a free-rider on the lobbying efforts of others (Walter and Jones, 1981). The actual outcome of protection-seeking activity is conditioned by a variety of political considerations as well. For instance, politicians may be constrained by the possibility of repercussions from groups adversely affected by protection, including consumers and export-oriented industries. Foreign competitors are also affected, so that issues concerning foreign relations enter into the decision process. In addition, politicians may be influenced more generally by ideology, party platforms, or attitudes toward equity. A number of researchers, including Ball (1967), Fieleke (1976), Clark (1980), and Ray (1981a, 1981b), have verified that a significant positive correlation exists between nominal tariff rates (or effective rates of protection) across manufacturing industries and low skilled-labor intensity, taken to be an indicator of the intensity of import competition and thus related to the size of the rents that could be obtained by protection.' Cheh (1974) and Bale (1977) analyzed the determinants of the percentage reductions in rates of duty resulting from the Kennedy Round tariff cuts, concluding that the cuts were determined in such a way as to minimize labor adjustment costs (see also Allen, Lewis, and Tower (1980)). Marvel and Ray (1983) also explored the determinants of Kennedy Round tariff cuts, finding the size of tariff cuts tended to be smaller if an industry was more concentrated or sold a larger fraction of its output to household consumers, and larger if the industry was more intensive in research and development (R & D) or more highly unionized. The result for R & D presumably represents the desire at the industry level for improved access to export markets achievable through larger reciprocal reductions in protection on the part of foreign countries. Along somewhat different lines, Baldwin (1976) analyzed several key Congressional votes on the Received for publication November 21, 1983. Revision accepted for publication December 14, 1984. *New York University. The authors are grateful to Robert Lipsey, Robert J. Levenson, J. Peter Jarrett, and James Green for providing data that contributed to this study, to Jang Ro Lee, Ashok Chatterjee, and Monica Kaufmann for research assistance, and to Bill Greene for providing advice on the estimation technique and computer program used to perform the statistical analysis. Thomas A. Pugel is also grateful for the support of an Esmee Fairbaim Research Fellowship at the University of Reading. 1 In both studies Ray also explores nontariff barriers (NTBs) across U.S. manufacturing industries. Aside from finding a positive relationship between tariff rates and NTBs, the results are not easily interpreted. However, there is some inferential evidence in Walter (1971), which finds a significant positive relationship between NTB incidence and (presumably relatively low-skill-intensive) developing country exports.